Integrated Transcriptomic and Proteomic Analyses of the Interaction Between Chicken Synovial Fibroblasts and Mycoplasma synoviae - Liu, Rui; Xu, Bin; Yu, Shengqing; Zhang, Jingfeng; Sun, Huawei; Liu, Chuanmin; Lu, Fengying; Pan, Qunxing; Zhang, Xiaofei (Frontiers in Microbiology, 2020)
Mycoplasma synoviae (MS), which causes respiratory disease, eggshell apex abnormalities, infectious synovitis, and arthritis in avian species, has become an economically detrimental poultry pathogen in recent years. In China, the disease is characterized by infectious synovitis and arthritis. However, the mechanism by which MS causes infectious synovitis and arthritis remains unknown. Increasing evidence suggests that synovial fibroblasts (SF) play a key role in the pathogenesis of arthritis. Here, both RNA-Seq and tandem mass tag (TMT) analyses are utilized to compare the response of primary chicken SF (CSF) following infection with and without MS. The host response between non-infected and infected cells was remarkably different at both the mRNA and protein levels. In total, 2,347 differentially expressed genes (DEGs) (upregulated, n = 1,137; downregulated, n = 1,210) and 221 differentially expressed proteins (DEPs) (upregulated, n = 129; downregulated, n = 92) were detected in the infected group. A correlation analysis indicated a moderate positive correlation between the mRNA and protein level changes in MS-infected CSF. At both the transcriptomic and proteomic levels, 149 DEGs were identified; 88 genes were upregulated and 61 genes were downregulated in CSF. Additionally, part of these regulated genes and their protein products were grouped into 7 categories: proliferation-related and apoptosis-related factors, inflammatory mediators, proangiogenic factors, antiangiogenic factors, matrix metalloproteinases, and other arthritis-related proteins. These proteins may be involved in the pathogenesis of MS-induced arthritis in chickens. To our knowledge, this is the first integrated analysis on the mechanism of CSF-MS interactions that combined transcriptomic and proteomic technologies. In this study, many key candidate genes and their protein products related to MS-induced infectious synovitis and arthritis were identified.